Pengaruh Shopping Lifestyle, Celebrity Endorser Dan Word Of Mouth Terhadap Keputusan Pembelian Make Up Luxcrime Di Kota Malang - Yulia, Fadila Hilma; Hidayati, Nur; Dianawati, Eris (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine and analyze the effects of shopping lifestyle (X1), celebrity endorser, and word of mouth (X3) on purchasing decisions. The research method used is a quantitative approach with a causal research design. The sampling technique is purposive sampling with a total of 112 respondents. The respondents in this study are Luxcrime make up consumers in Malang City. The data analysis method used is multiple linear regression analysis with SPSS 25 as the analysis tool. The results of this study explain that shopping lifestyle, celebrity endorser, and word of mouth have a positive and significant impact on purchasing decisions. Keywords: Shopping Lifestyle, Celebrity Endorser, Word Of Mouth, And Purchasing Decisions